2023
DOI: 10.1111/tra.12883
|View full text |Cite
|
Sign up to set email alerts
|

N‐BAR and F‐BAR proteins—endophilin‐A3 and PSTPIP1—control clathrin‐independent endocytosis of L1CAM

Abstract: Recent advances in the field demonstrate the high diversity and complexity of endocytic pathways. In the current study, we focus on the endocytosis of L1CAM. This glycoprotein plays a major role in the development of the nervous system, and is involved in cancer development and is associated with metastases and poor prognosis. Two L1CAM isoforms are subject to endocytosis: isoform 1, described as a clathrinmediated cargo; isoform 2, whose endocytosis has never been studied. Deciphering the molecular machinery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 98 publications
1
3
0
Order By: Relevance
“…Our hypothesis is that endoA3 uptakes Prominin-1 from the cell surface during photoreceptors' development and once they mature, the interaction ceases, releasing Prominin-1 to the OSs, where it may play a role in OSs disk morphogenesis as highlighted by studies in Prom1-knockout mice 18,42 . Supporting this hypothesis, we found that the tumour marker CD166 is a clathrin-independent endocytosis cargo that is internalized in an endoA3-dependent manner 49,50 . As Prominin-1 and CD166…”
Section: Discussionsupporting
confidence: 59%
“…Our hypothesis is that endoA3 uptakes Prominin-1 from the cell surface during photoreceptors' development and once they mature, the interaction ceases, releasing Prominin-1 to the OSs, where it may play a role in OSs disk morphogenesis as highlighted by studies in Prom1-knockout mice 18,42 . Supporting this hypothesis, we found that the tumour marker CD166 is a clathrin-independent endocytosis cargo that is internalized in an endoA3-dependent manner 49,50 . As Prominin-1 and CD166…”
Section: Discussionsupporting
confidence: 59%
“…Overall, the interplay between N-BAR and F-BAR proteins and their interaction with other cellular components form an intricate regulatory network that governs membrane dynamics, tubule formation, and actin regulation. These processes are essential for various cellular functions, including endocytosis, cell migration, and vesicular trafficking [ [26] , [27] , [28] ]. Previous findings suggest that N-BAR and F-BAR domain-containing proteins are segregated and localized to distinct tubules within the cells [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Aside from these, new studies continue to reveal additional cargos that will likely allow us to better understand selection mechanisms during CME and CIE. For example, amyloid precursor protein (APP) and low-density lipoprotein internalize when clathrin and dynamin are inhibited, suggesting roles for an as-yet undetermined CIE route ( Aow et al, 2022 ). Similarly, uptake of L1CAM and CD166 through Endophilin-A3-mediated CIE may facilitate studies of pathways such as FEME or UFE ( Renard et al, 2019 ; Lemaigre et al, 2022 ).…”
Section: Discussion: Future Directions In Ciementioning
confidence: 99%